Immunotactoid glomerulopathy: A rare glomerular disease case study - Dzekova Vidimliski, Pavlina; Karanfilovski, Vlatko; Ristovska, Vesna; Gjorgjievski, Nikola; Nikolov, Igor; Petrushevska, Gordana (Medknow, 2022)
Immunotactoid glomerulopathy (ITG) is a rare glomerular disease with variable responsiveness to the immunosuppressive therapy and with uncertain prognosis. ITG was diagnosed in two patients with type 2 diabetes mellitus with nephrotic syndrome and chronic kidney disease. The absence of diabetic retinopathy in the first case and the recent onset of diabetes in the second case accompanied with sudden increase in the 24‑hour proteinuria and rapid decline in kidney function, prompted us to perform kidney biopsy. The electron microscopy set the diagnosis of ITG in both cases. There is no consensus for the treatment of ITG. The first patient was treated with combination of steroids and mycophenolate mofetil with reduction of the 24‑hour proteinuria, but with persistence of the chronic kidney disease. The second patient received high doses of steroids with continuous deterioration of kidney function with the need of hemodialysis treatment.
Keywords: Chronic kidney failure; electron microscopy; glomerulonephritis; immunosuppression therapy; nephrotic syndrome